Шадр - Воронова Ольга Порфирьевна (Жизнь замечательных людей, 1969)
Экземпляры: ИСК (20111024) / Инвентарный номер: 479037 / Цена: 0.77 / Сис.шифр: 85.133(2)7-8 / Авт.знак: В 75 / ГРНТИ: 18 / ББК: 85.133(2)7-8